Young men's sports betting assemblages: masculinities, homosociality and risky places. (24th March 2022) - Waitt, Gordon; Cahill, Hayden; Gordon, Ross
ABSTRACT: Place and gender are key notions for interpreting gambling. Canvassing the work of Deleuze and Guattari, this article elaborates the concept of sports betting assemblages to better understand the everyday geographies of gambling. The account draws on a sensory ethnography with young men who use smartphone sports betting applications in the context of the regional city of Wollongong, Australia. It asks what geographers can contribute to gambling studies when sports betting and the socio-material arrangements that constitute them are conceived as essential components of place and gender. Our aim is to open debates about sports betting and risk beyond a conventional focus on genetics, psychological makeup, social structures and representations. Particular attention is given to the emotional and affective geographies found in the making and unmaking of sports betting using smartphone betting applications. We argue that paying attention to emotions and affective geographies is critical if accounts of sports betting applications are to move beyond simplified biological or representational accounts.